Clinical Features and Outcomes of Pediatric Monophasic and Recurrent Idiopathic Optic Neuritis. (January 2020) - Jonzzon, Soren; Suleiman, Leena; Yousef, Andrew; Young, Brenda; Hart, Janace; Peschl, Patrick; Reindl, Markus; Schaller, Kristin L.; Bennett, Jeffrey L.; Waubant, Emmanuelle; Graves, Jennifer S.
Limited data exist on isolated optic neuritis in children. We report the clinical features and treatment of pediatric subjects with monophasic and recurrent idiopathic optic neuritis. This retrospective cohort study of patients with isolated optic neuritis identified 10 monophasic and 7 recurrent optic neuritis cases. Monophasic optic neuritis patients were older (mean 13.3 ± 4.22) than those with recurrent idiopathic optic neuritis (9.86 ± 3.63). Females represented 50% of monophasic and 85.7% of recurrent idiopathic optic neuritis cases. Patients with monophasic optic neuritis were less likely to have a bilateral onset than recurrent idiopathic optic neuritis (40% vs 57.1%). Only 1 case had oligoclonal bands in the cerebrospinal fluid CSF. Most recurrent idiopathic optic neuritis cases had evidence of anti–myelin oligodendrocyte glycoprotein (MOG) antibodies (5/7). Treatment of recurrent idiopathic optic neuritis cases included intravenous pulse glucocorticosteroids and immunotherapy. We observed differences between recurrent and monophasic idiopathic optic neuritis. Immunosuppression appeared to prevent further relapses in recurrent idiopathic optic neuritis patients. Weaning immunotherapies after several years of quiescence in recurrent idiopathic optic neuritis may be possible, but larger studies are needed.